Non-Typical learning sites: A railway platform and an interplay between foreground, uncertainty, and hope - Marcone, Renato [UNESP]; Bose, Arindam; Milani, Raquel [UNESP]; Kumar, Varun (FapUNIFESP (SciELO), 2024)
After watching the groups of boys studying at the stairs of a suburban railway station in Mumbai for a while, we decided to talk to those students in order to understand their choice for such an unusual place of study. Adopting an eclectic exploratory approach, this paper argues that such impromptu places of collective learning are often guided by the prospects of inter and intra peer group learning and tend to redefine young students’ foregrounds who handle their financial disadvantaged conditions to come out of their background, empowering themselves and achieving autonomy. This paper hypothesises that this railway platform provides opportunities to those whose performance in formal education remained poor and to those who could not afford the capitalist market of private tuitions (additional academic coaching other than in schools for getting an edge in examinations) thereby missing out on future scope. Despite the gender disparity, such impromptu places of learning also tend to resist the enculturation process of the dominant cultural capital and it also creates an interplay between uncertainties, hopes, and foreground as well.
Locais de aprendizagem atípicos: uma plataforma ferroviária e uma interação entre foreground, incerteza e esperança
Keywords: Critical Mathematics Education; Cultural Capital; Dialogue; Foreground; Non-Typical learning sites